2006 International Conference on Image Processing 2006
DOI: 10.1109/icip.2006.312959
|View full text |Cite
|
Sign up to set email alerts
|

High Dynamic Range Images as a Basis for Detection of Argyrophilic Nucleolar Organizer Regions Under Varying Stain Intensities

Abstract: Silver staining of cytopathologic specimens offers advantages in cancer diagnostics. A difficulty with such stained cell specimens is the very high dynamic range needed by the imaging system to appropriately cover the varying stain intensities. Beside those images of cell nuclei that can be used for the diagnostic interpretation, there are nuclei that appear too dark to observe their relevant properties, the so-called argyrophilic nucleolar organizer regions (AgNORs), which appear as spot-like areas darker tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…A considerable improvement in the diagnostic performance of AgNOR analysis is expected from a novel, automatic AgNOR segmentation process, which not only counts but also will yield area measurements of AgNORs. This new procedure makes use of high‐dynamic‐range images 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable improvement in the diagnostic performance of AgNOR analysis is expected from a novel, automatic AgNOR segmentation process, which not only counts but also will yield area measurements of AgNORs. This new procedure makes use of high‐dynamic‐range images 23…”
Section: Discussionmentioning
confidence: 99%
“…We applied the MMCA process to smears from oral brush biopsies, combining conventional cytology with the more quantifiable DNA content, followed by a count of argyrophilic nucleolar organizing regions (AgNORs) to identify early malignant transformation 14‐20. Recent studies have demonstrated that the number and/or size of AgNORs correlate with the ribosomal gene activity and, therefore, with cellular proliferation and consequent malignant potential 21‐24…”
mentioning
confidence: 99%
“…An alternative weighting function is the derivative of the CTF f (), 1, 13 which is similar to our weighting function. However, since our CTF is rather linear, the critical border areas would have a too strong influence and so we use the more stringent weighting function in (13) instead.…”
Section: Estimationmentioning
confidence: 99%
“…of the group g i , the covariance matrix C C = 1 μ 00 μ 20 μ 11 μ 11 μ 02 (5) and the corresponding larger eigenvalue λ 1 and eigenvector v 1 , with C · v 1 = λ 1 · v 1 , can be calculated. This then allows to estimate the orientation of an elliptic approximation for g i by…”
Section: Region Groupingmentioning
confidence: 99%
“…In previous work we have developed methods to automatically analyze AgNORs [5,6]. This analysis in turn requires that the nuclei have to be segmented and detected within the microscopy images first.…”
Section: Introductionmentioning
confidence: 99%